2020
DOI: 10.18632/aging.103836
|View full text |Cite
|
Sign up to set email alerts
|

Systemic analyses of expression patterns and clinical features for GIMAPs family members in lung adenocarcinoma

Abstract: GTPase of immunity-associated proteins (GIMAPs) are frequently prescribed as important components of immune regulation complexes, which were known to play key roles in lung adenocarcinoma. However, little is known about the function of distinct GIMAPs in lung adenocarcinoma. To address this issue, this study investigated the biological function and pathway of GIMAPs in lung adenocarcinoma using multiple public databases. Absent expression of GIMAPs was found in lung adenocarcinoma at mRNA and protein levels. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The invasion and migration of tumor cells lead to the poor prognosis and recurrence of diseases. Studies have shown that the imbalance of GIMAP family expression is related to the development of lung cancer ( 30 , 31 ). Based on the prognostic value of the GIMAP family in lung cancer, it is possible to understand the mechanism driving the occurrence and development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion and migration of tumor cells lead to the poor prognosis and recurrence of diseases. Studies have shown that the imbalance of GIMAP family expression is related to the development of lung cancer ( 30 , 31 ). Based on the prognostic value of the GIMAP family in lung cancer, it is possible to understand the mechanism driving the occurrence and development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Studies on the association of GIMAPs with individual cancers and diseases have identified the GIMAP family as a potential diagnostic and prognostic biomarker of lung adenocarcinoma. 6 Additionally, the dysregulation of GIMAP5 and GIMAP6 has been reported in hepatocellular carcinoma. GIMAP family is also closely related to tumour immunity.…”
Section: Introductionmentioning
confidence: 99%
“…GIMAP 1 and GIMAP 6 have a fundamental role in maintaining the quantity of CD8+ T cells [17,21]. A positive correlation of all GIMAP family members with CD8+ T cell infiltration in lung cancer has been demonstrated [32]. GIMAP7 also has a positive correlation with CD8+ T cell infiltration in pancreatic adenocarcinoma [33].…”
Section: Discussionmentioning
confidence: 96%